Downlink channel analysis at multi-cell massive MIMO: novel adaptive channel allocation scheme - Sandeep Dhanraj Bawage; Manjula Shivkumar (Institute of Advanced Engineering and Science, 2022)
In large multiple-input multiple-output (MIMO) systems, we offer a new access strategy for crowd situations. Crowd situations include a high number users who have intermittent access patterns, making orthogonal scheduling impossible. In this paper, the work is driven by the massive MIMO problem at crowded environment. The pilot contamination problem is dependent on the protocol assumptions is observed in the system. We investigate a crowd situation in which the users number and their access behaviours make scheduling broadcasts impossible. The pilot assignment is time-slot randomized, but the data portion is repeated, allowing it to use successive-interference-cancellation across copies of comparable packets. In result analysis, the transmission of downlink to the user has shown with changing the number of users, fading effect, transmission power and the number of base station antennas.